RELEVANCE OF THE CONCEPT OF MULTICULTURALISM EDUCATION ACCORDING TO M QURAISH SHIHAB TO ISLAMIC EDUCATION OF EARLY CHILDREN - Asiyah Asiyah (Jurnal Pendidikan "EDUKASIA MULTIKULTURA", 2020)
The purpose of this study (1) To describe the concept of multiculturalism according to M. Quraish Shihab in the book Tafsir Al-Misbah. (2) To determine its relevance to Islamic education in early childhood. This type of research is literature research or literature research, the results of research on the Concept of Multiculturalism Education According to M Quraish Shihab and its Relevance to Early Childhood Islamic Education is the concept of multicultural education, there are 3 concepts, namely Ta'aruf (Knowing each other), the stronger the recognition of one party to the other. , the more open opportunities for mutual benefit. Egalitarian (Equation of Degrees), there is no difference between one term and another. Takwa (degree of piety) Humans have a tendency to seek and even compete and compete to be the best. The relevance of multiculturalism education to early childhood Islamic education, multiculturalism education according to M. Quraish Shihab is very good to be applied to early childhood Islamic education because of its very good relevance, by implementing multiculturalism education children will have a very good personality foundation to make the basis of the phase towards maturity